(Ba, Ca)(Zr, Ti)O3 lead-free piezoelectric ceramics—The critical role of processing on properties. Issue 13 (November 2015) - Bai, Yang; Matousek, Ales; Tofel, Pavel; Bijalwan, Vijay; Nan, Bo; Hughes, Hana; Button, Tim W.
Abstract: Lead-free piezoelectric compositions based on (Ba, Ca)(Zr, Ti)O3 have been reported to exhibit many piezoelectric properties similar to the conventionally used Pb(Zr, Ti)O3 materials, and have thus been attracting much attention as potential replacements for lead-based piezoceramics. However, there appears quite a wide variation in the reported piezoelectric properties of the BCZT ceramics, indicating that such properties may be sensitive to fabrication and processing methods. This paper reports an investigation of a wide range of processing factors, including composition (e.g. ratio of Ba(Zr, Ti)O3 to (Ba, Ca)TiO3 ), sintering conditions (temperature and cooling rate), particle size of the calcined ceramic powder, structure and microstructure (e.g. phase, lattice parameters, density and grain size), and their effect on the piezoelectric properties. For individual compositions, lattice constants and grain size, which are themselves dependent on the ceramic powder particle size and sintering conditions, have been shown to be very important in terms of optimising piezoelectric properties in these materials.